Exon skipping and translation in patients with frameshift deletions in the dystrophin gene. - Sherratt, T G (1993)
Although many Duchenne muscular dystrophy patients have a deletion in the dystrophin gene which disrupts the translational reading frame, they express dystrophin in a small proportion of skeletal muscle fibers ("revertant fibers"). Antibody studies have shown, indirectly, that dystrophin synthesis in revertant fibers is facilitated by a frame-restoring mechanism; in the present study, the feasibility of mRNA splicing was investigated. Dystrophin transcripts were analyzed in skeletal muscle from individuals possessing revertant fibers and a frameshift deletion in the dystrophin gene. In each case a minor in-frame transcript was detected, in which exons adjacent to those deleted from the genome had been skipped. There appeared to be some correlation between the levels of in-frame transcripts and the predicted translation products. Low levels of alternatively spliced transcripts were also present in normal muscle. The results provide further evidence of exon skipping in the dystrophin gene and indicate that this may be involved in the synthesis of dystrophin by revertant fibers.